The Role of the Social Worker at Social Institutions in Empowering Battered Women: A Study from Amman - Abu Jalambo , Dina Jamal Ramadan; Akroush, Lubna Judah (Dirasat: Human and Social Sciences, 2024)
Objectives: This study investigates the role of the social worker in empowering battered women in social institutions in the city of Amman. Methods: We study this question through quantitative methods, specifically survey interviews. The study sample consists of (160) women who were present in social institutions in the city of Amman, and they are within the age group of (20 years - 51 years and over), from four institutions, namely: the Jordanian Women’s Union, the Jordanian Women’s Solidarity Institute Association, and Dar Family Reconciliation, and Dar Amna. Results: The results demonstrate that the role of the social worker in social and psychological empowerment came at a high level, as the social worker has a role in introducing them to their rights, legal procedures, and existing penalties. The results also showed that the role of the social worker in psychological empowerment was to help them overcome feelings of fear and to obtain psychological support from their families. Further, the results of the study showed that the role of the social worker in economic empowerment was at a low level, as his role was limited to empower them economically. Conclusions: The study recommended increasing women’s awareness of their rights when they face any violence type and conducting many studies that could represent an extension in the field of the phenomenon of violence against women.